New Adaptive Feature in Dolichandrone spathacea (L.f.) K. Schum (Bignoniaceae) - Patil, Kamlakar H.; Toro, Sunita V.; Gokhale, Mahesh V.; Kambhar, Sidanand V. (Indian Forester, 2023)
The Dolichandrone spathacea (L. f.) Seem. is a species of Bignoniaceae. In a swampy environment, the plant displays morpho-physiological adaptations. The findings showed that salt glands are found in all aerial parts, including leaves, branches, and reproductive organs like flowers and seeds. It is regarded as a new adaptive characteristic in the species. The number of salt glands present in each portion, their size in the leaf, the amount of chloride present, and their osmotic potential value has all been used to evaluate the dispersion of these glands. One of the necessary modifications to survive in this habitat is the presence of salt glands. This is an adaptation that helps organisms thriving in salty environments with few freshwater supplies maintain a healthy salt balance.